Invariant manifolds for coupled nonlinear parabolic-hyperbolic partial differential equations - Fastovska, T. B. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We consider an abstract system of coupled nonlinear parabolic-hyperbolic partial differential equations. This system describes, e.g., thermoelastic phenomena in various physical bodies. Several results on the existence of invariant exponentially attracting manifolds for similar problems were obtained earlier. In the present paper, we prove the existence of such an invariant manifold under less restrictive conditions for a broader class of problems.